Neuropsychiatric Events in Systemic Lupus Erythematosus: Predictors of Occurrence and Resolution in a Longitudinal Analysis of an International Inception Cohort. Issue 12 (29th October 2021) - Hanly, John G.; Gordon, Caroline; Bae, Sang‐Cheol; Romero‐Diaz, Juanita; Sanchez‐Guerrero, Jorge; Bernatsky, Sasha; Clarke, Ann E.; Wallace, Daniel J.; Isenberg, David A.; Rahman, Anisur; Merrill, Joan T.; Fortin, Paul R.; et al.
Abstract : Objective: To determine predictors of change in neuropsychiatric (NP) event status in a large, prospective, international inception cohort of patients with systemic lupus erythematosus (SLE). Methods: Upon enrollment and annually thereafter, NP events attributed to SLE and non‐SLE causes and physician‐determined resolution were documented. Factors potentially associated with the onset and resolution of NP events were determined by time‐to‐event analysis using a multistate modeling structure. Results: NP events occurred in 955 (52.3%) of 1, 827 patients, and 593 (31.0%) of 1, 910 unique events were attributed to SLE. For SLE‐associated NP (SLE NP) events, multivariate analysis revealed a positive association with male sex ( P  = 0.028), concurrent non‐SLE NP events excluding headache ( P < 0.001), active SLE ( P = 0.012), and glucocorticoid use ( P = 0.008). There was a negative association with Asian race ( P = 0.002), postsecondary education ( P = 0.001), and treatment with immunosuppressive drugs ( P = 0.019) or antimalarial drugs ( P = 0.056). For non‐SLE NP events excluding headache, there was a positive association with concurrent SLE NP events ( P < 0.001) and a negative association with African race ( P = 0.012) and Asian race ( P < 0.001). NP events attributed to SLE had a higher resolution rate than non‐SLE NP events, with the exception of headache, which had comparable resolution rates. For SLE NP events, multivariate analysis revealed that resolution was more common in patients of Asian race ( P = 0.006) and for central/focal NP events ( P < 0.001). For non‐SLE NP events, resolution was more common in patients of African race ( P = 0.017) and less common in patients who were older at SLE diagnosis ( P < 0.001). Conclusion: In a large and long‐term study of the occurrence and resolution of NP events in SLE, we identified subgroups with better and worse prognosis. The course of NP events differs greatly depending on their nature and attribution.